Knowledge and ambidexterity’s impact on product innovation - Del Carpio, Javier Fernando (2022)
This paper aims to evaluate the relationship between external sources of knowledge and innovation ambidexterity and then analyze how innovation ambidexterity improves product innovation. This study presents evidence based on a sample of 355 low-medium-tech (LMT) firms that participated in the National Survey of Innovation in the Manufacturing Industry and Knowledge-Intensive Service Firms in Peru. A structural equation model approach was applied. The results indicate that there is a positive relationship between external sources of knowledge and exploration and exploitation improves product innovation. These results provide deeper knowledge about how LMT firms in an emerging economy can apply open innovation practices to develop innovation ambidexterity, thus improving their product innovation capability.